Modernização, fragilização e a apropriação da renda agrícola pela agricultura familiar mineira nos anos 2000 - Mendes, Samantha Rezende (2013)
This work aims to investigate the evolution of the compositional structure of the participation of family occupational groups of rural areas from Triângulo Mineiro engaged in agricultural activities in the income of the sector. Therefore, we use a statistical method Decomposition of Change in Agricultural Income of different family occupational groups (employers, employees and self-employed, agricultural and pluriactive) based on microdata from PNAD / IBGE in the period 2002-2009. The hypothesis guiding this study was constructed from the results of field trials carried out in four municipalities of Triângulo Mineiro and Alto Parnaíba where we detected a situation of fragility and latent abandonment of agricultural activities by farmers municipalities surveyed. So, we argue here that this reality is not only restricted to the municipalities surveyed, but that much of the family farm in Minas Gerais lies fragile in important ways. The evidence presented by the data confirm the hypothesis of this study, since families are self-employed (they represent the majority of farmers) less appropriate the surplus of agricultural income generated in the state of Minas Gerais generating a framework of greater fragility of these families with a strong trend of abandonment of agricultural activity. This movement would tend to deepen as the agricultural development model promoted in this region in search of efficiency standards and given the competition in the industry, would force the output of those farmers who do not get the same productivity standards. Thus, public policies such as PRONAF, PAA and PNAE fulfill an important role in reducing the abandonment of farming by the farmers process.